Effect of Postpartum Gymnastics on Decreasing Height of Uterine Fundus in Post Partum Mothers in BPM Midwife Susi Irma Navia, S.ST Bengkulu City - Vellyza Colin; Buyung Keraman; Atika Dwi Sundari (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2019)
One of causes of the high maternal mortality rate by Indonesia Demographic Health Survey (IDHS) is post-partum haemorrhage (20%). No smooth involution adversely affects postpartum bleeding. Early ambulation such as postpartum exercise facilitates a normal involution. This study aims to study the effect of puerperal gymnastics on the reduction of uterine fundus height among post partum mothers at BPM Bidan Susi Irma Navia, S.ST Bengkulu City. This study used a pre experiment design. The population in this study were all postpartum mothers in BPM Bidan Susi Irma Navia, S.ST Bengkulu City on June 22-July 22 2018 as many as 24 mothers. The sample in this study there were 2 groups, namely the maternal maternal experimental sample that did postpartum gymnastics and the non-maternal maternity samples which did not do puerperal gymnastics. The results of the study were: (1) In mothers who did not do childbirth, on the third day the minimum uterine fundal height was 7 cm, uterine fundus height was maximum 10 cm and uterine fundal height was an average of 8.50 cm with a standard deviation of 1.087. While on day 5, the minimum uterine fundus was 4 cm, uterine fundus height was maximum 8 cm and uterine fundal height was 5.67 cm with a standard deviation of 1.073; (2) In women who had postnatal exercise, on the third day of fundus height the minimum uteri is 7 cm, uterine fundus height is maximum 9 cm and uterine fundal height is an average of 7.83 cm with a standard deviation of 0.718. Whereas on day 5 the uterine fundal height was minimum 3 cm, uterine fundus height maximum 5 cm and uterine fundal height averaged 4.00 cm with a standard deviation of 0.739; (3) On the 3rd day there was no postpartum exercise effect on the decrease in uterine fundus height in post partum mothers at BPM Bidan Susi Irma Navia, S.ST Bengkulu City; (4) On the 5th day there was the influence of puerperal gymnastics on decreasing uterine fundus height in post partum mothers at BPM Bidan Susi Irma Navia, S.ST Bengkulu City.Keywords: fundus uteri, postpartum gymnastics, postpartum mother